Tauopathy contributes to synaptic and cognitive deficits in a murine model for Alzheimer's disease. Issue 6 (6th March 2014) - Stancu, Ilie‐Cosmin; Ris, Laurence; Vasconcelos, Bruno; Marinangeli, Claudia; Goeminne, Léonie; Laporte, Vincent; Haylani, Laetitia E.; Couturier, Julien; Schakman, Olivier; Gailly, Philippe; Pierrot, Nathalie; Kienlen‐Campard, Pascal; et al.
ABSTRACT: Tau alterations are now considered an executor of neuronal demise and cognitive dysfunction in Alzheimer's disease (AD). Mouse models combining amyloidosis and tauopathy and their parental counterparts are important tools to further investigate the interplay of abnormal amyloid‐β (Aβ) and Tau species in pathogenesis, synaptic and neuronal dysfunction, and cognitive decline. Here, we crossed APP/PS1 mice with 5 early‐onset familial AD mutations (5xFAD) and TauP301S (PS19) transgenic mice, denoted F + /T + mice, and phenotypically compared them to their respective parental strains, denoted F + /T – and F – /T + respectively, as controls. We found dramatically aggravated tauopathy ( 10‐fold) in F + /T + mice compared to the parental F – /T + mice. In contrast, amyloidosis was unaltered compared to the parental F + /T – mice. Tauopathy was invariably and very robustly aggravated in hippocampal and cortical brain regions. Most important, F + /T + displayed aggravated cognitive deficits in a hippocampus‐dependent spatial navigation task, compared to the parental F + /T – strain, while parental F – /T + mice did not display cognitive impairment. Basal synaptic transmission was impaired in F + /T + mice compared to nontransgenic mice and the parental strains (≥40%). Finally, F + /T + mice displayed a significant hippocampal atrophy ( 20%) compared to nontransgenic mice, in contrast to the parental strains. Our data indicate for the first time that pathological Aβ species (or APP/PS1) induced changes in Tau contribute to cognitive deficits correlating with synaptic deficits and hippocampal atrophy in an AD model. Our data lend support to the amyloid cascade hypothesis with a role of pathological Aβ species as initiator and pathological Tau species as executor.—Stancu, I.‐C., Ris, L., Vasconcelos, B., Marinangeli, C., Goeminne, L., Laporte, V., Haylani, L. E., Couturier, J., Schakman, O., Gailly, P., Pierrot, N., Kienlen‐Campard, P., Octave, J.‐N., Dewachter, I. Tauopathy contributes to synaptic and cognitive deficits in a murine model for Alzheimer's disease. FASEB J . 28, 2620–2631 (2014). www.fasebj.org